THE PROBLEM OF RATIONALIZATION OF SOCIAL INTERACTION IN THE CONTEXT OF POSTMODERN - SOGHOMONYAN, GAGIK (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
In the face of uncertainty, the rationalization becomes an objective obligation for the adaptation to global transformations and to new social conditions. In the postmodern society, where uncertainty has become a stable form of life, the rationalization of social interactions is carried out in the following ways: symbolizing the relations of ex-change (replacing reality with the symbols of reality), McDonaldization of social interactions (efficiency, calculation, predictability, control) and the theatricalisation of social interactions (game behavior, which is alien to universal norms and values). Keeping in mind the fact that every way of organizing and regulation social activity reflects a certain rationalization system, which forms a particular culture, the author concludes that the ratio must be cleared from unlawful claims, authoritative ambitions, from all the superficial, witch comes from politic and the struggle of human interests. The process of rationalization should have its own clear sociocultural boundaries and necessarily be inscribed in the wider spiritual and humanistic context of culture. The ultimate goal of rationalization of social interactions should be the provision of a dignified and happy life for the crown of creation – Human.
Keywords: the individualized society, uncertainty, risk, rationalization, a new rationality, symbolization of exchange relations, MacDonald΄s social interactions, gamification of social interactions